2022
DOI: 10.33594/000000496
|View full text |Cite
|
Sign up to set email alerts
|

Arbutus Unedo Honey and Propolis Ameliorate Acute Kidney Injury, Acute Liver Injury, and Proteinuria via Hypoglycemic and Antioxidant Activity in Streptozotocin-Treated Rats

Abstract: BACKGROUND/AIMS: Honey and propolis have biological and therapeutic effects in various pathological and clinical conditions such as hyperglycemia and diabetes. However, the combined use of honey and propolis has not been reported. The study evaluated the protective effect of Arbutus unedo honey, propolis and their combination in streptozotocin (STR)-induced hyperglycemia, acute kidney injury (AKI), liver injury, dyslipidemia, and proteinuria in male Wistar rats. METHODS: The study identified physicochemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…However, treatment with SBME in our study significantly suppressed MDA levels in STZ-induced diabetic rats; this could help reduce oxidative stress. Our findings were consistent with those of other studies that indicated that SBH improved the MDA level in diabetic rats[ 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, treatment with SBME in our study significantly suppressed MDA levels in STZ-induced diabetic rats; this could help reduce oxidative stress. Our findings were consistent with those of other studies that indicated that SBH improved the MDA level in diabetic rats[ 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…This great variety of natural products has been intensively researched and employed in different industries for various purposes [ 2 , 3 , 4 ]. For example, propolis and bee venom are the subjects of important research in the field of pharmacy due to their strong biological activities [ 5 , 6 ], while honey, bee pollen, and bee bread are considered important products as functional foods due to their nutritional values and remarkable biological activities [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%